1974
DOI: 10.1021/jo00918a017
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of 1,4-quinone N,N'-dibenzenesulfonylimines, 1,4-quinones, and 1,4-quinone N,N'-dibenzoylimines with secondary diazo compounds. Structures of alleged arocyclopropenes

Abstract: 1,4‐Benzochinon‐N,N′‐dibenzolsulfonylirnin (I) und das Naphthochinon‐Analogon (IV) reagieren mit Diphenyldiazomethan (II) zu den Addukten (III) bzw. (V).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 4 publications
0
7
0
Order By: Relevance
“…Treatment of 43 with fert-butoxide affords 39b directly but in low yield. 32 The formation of 1,6methano [10]annulene from 44 under essentially the same reaction conditions has been described,35 and an analogous path involving a bridgehead olefin is likely to operate; base-catalyzed epimerization at C12 is pre- Billups procedure is unlikely to succeed when the endothermic migration of a tetrasubstituted olefinic linkage is required (cf. 45 -* 46) and/or when loss of HX can occur in two distinct ways.…”
Section: Synthesis Of the Cydoproparenesmentioning
confidence: 91%
See 3 more Smart Citations
“…Treatment of 43 with fert-butoxide affords 39b directly but in low yield. 32 The formation of 1,6methano [10]annulene from 44 under essentially the same reaction conditions has been described,35 and an analogous path involving a bridgehead olefin is likely to operate; base-catalyzed epimerization at C12 is pre- Billups procedure is unlikely to succeed when the endothermic migration of a tetrasubstituted olefinic linkage is required (cf. 45 -* 46) and/or when loss of HX can occur in two distinct ways.…”
Section: Synthesis Of the Cydoproparenesmentioning
confidence: 91%
“…Except for 39 and 41a (see below) each of these compounds results from a precursor in which the 7,7-dichlorobieyclo[4.1.0]hept-3-enyl moiety is in place. The [10]annulene derivatives 39a and 39b are formed from 42 and 43, respectively. While 42 may be regarded as SCHEME VI sumed to lead to 39b as the thermodynamically more stable isomer.…”
Section: Synthesis Of the Cydoproparenesmentioning
confidence: 99%
See 2 more Smart Citations
“…The title compound was reported (Mustafa & Kamel, 1953) to form a substituted benzocyclopropene, (1), which would have been possibly the earliest synthesis (Anet & Anet, 1964;Vogel et al, 1965) of this type of unique structure. On the basis mainly of spectroscopic evidence (Pinkus & Tsuji, 1974;Jones et al, 1974), the product was instead suggested to be a bicylic structure, (2), of a three-membered ring fused to a sixmembered one [Halton, 1973; since this review was published before the papers by Pinkus & Tsuji (1974) and Jones et al (1974) appeared, these two references, which deal with the correction of the report by Mustafa & Kamel (1953), do not appear in the review; the numbering of the bicyclic compound without substituents is given in the Halton reference] {named by Chem. Abstr.…”
Section: Commentmentioning
confidence: 99%